Coping Strategies of Parents Facing Social Stigma for Having Children with ADHD - Yusnia, Vira; Kurniadewi, Elisa (Education : Jurnal Sosial Humaniora dan Pendidikan, 2025)
Children with Attention Deficit Hyperactivity Disorder (ADHD) often experience social stigma from their surroundings due to behaviors perceived as deviant. This stigma not only affects the children but also extends to their parents as the primary caregivers. This study aims to explore the coping strategies used by parents of children with ADHD in dealing with social stigma. This research employs a qualitative method with a descriptive narrative approach. Data were collected through in-depth interviews, observation, and documentation. The study involved five informants, consisting of four parents of children with ADHD and one therapist for children with special needs. This study is guided by Lazarus and Folkman’s (1984) coping theory, which distinguishes between problem-focused coping and emotion-focused coping, as well as Link and Phelan’s (2001) social stigma theory, which explains how stigma operates through labeling, stereotyping, separation, status loss, and discrimination, sustained by power. The findings reveal that parents use a combination of both coping strategies to address the social stigma associated with having a child with ADHD. Problem-focused coping includes educating the surrounding community, communicating with schools, therapy and seeking information, social, or emotional support. Emotion-focused coping involves self-acceptance, spirituality, emotional regulation, distancing from stigmatizing environments. These coping strategies represent the parents’ adaptive responses to the social pressures caused by stigma. The study highlights the active role of parents in navigating societal judgments while supporting their child’s development and well-being. These findings contribute to a deeper understanding of how parents adapt to societal judgments and provide practical insight for support systems addressing families of children with ADHD.